Thymoma Causing Bilateral Upper Extremity Deep Vein Thrombosis. (2020) - Bui, Hoang; Helms, Jessica L.; Sierra-Hoffman, Miguel; Stevens, Mark L.; Deliz-Aguirre, Rafael; Castro-Lainez, Miriams T.; Deliz, Rafael J.
Abstract: A 38-year-old African American male presented with progressive pain, swelling, numbness, and warmth of the left upper extremity ten days before admission. A chest computerized tomography scan showed a large 8.3 cm × 6.1 cm x 9.9 cm anterior mediastinal mass with compression of the left brachiocephalic vein and superior vena cava. A venous doppler showed multiple occlusive venous thrombi in bilateral upper extremities, including the bilateral internal jugular and subclavian veins, as well as the left subclavian, axillary, cephalic, brachial and median cubital veins. Further laboratory workup came positive for acetylcholine receptor binding antibody suggesting myasthenia gravis, but the patient was asymptomatic for myasthenia gravis. A percutaneous core CT guided biopsy pathology resulted in a predominant T-cell population CD5 positive with few B cells; the immunophenotypic features suggested Type B2 thymoma. To the best of our knowledge, this case is the only reported thymoma presenting with bilateral deep vein thrombosis of the upper extremities. The deep vein thrombosis therapy was enoxaparin 1mg/kg subcutaneously every 12 hours and dexamethasone 4mg intravenously every 4 hours as an anti-inflammatory drug for thymoma related compression of the mediastinum. The patient was referred to a tertiary oncological medical center for a total thymectomy, chemotherapy, and adjuvant radiotherapy.